DESIGN OF THE CEILING ASSISTANCE - Wibowo, Sandi Yusuf Heri; Darto, Darto; Sunada, I Made (TRANSMISI, 2019)
Ceiling installation auxiliary tool is auxiliary tool for installing a ceiling with a simple method. Namely by placing the ceiling above the cross section and moving the gears to the ceiling can reach the desired height. This auxiliary tool is needed to help to lighten the workload and save the ceiling installation time. This auxiliary tool can reach places or rooms that have narrow access, because this tool can be dismantled pairs. This tool can hold the user load up to 80 kg and the weight of the ceiling up to 47.3 kg, so the total weight reached 127.3 kg. This auxiliary tool has four pedestal wheels that can move as desired.